The Influence of Phosphate Fertilizer and Plant Growth Regulators on the Growth and Yield of Ratoon Rice (Oryza sativa L.) Grown on Swampland - Fitri, Siti Nurul Aidil; Bernas, Siti Masreah; Sodikin, Erizal; Wijaya, Andi; Apriadi, Ferra (UNIVERSITY OF LAMPUNG, 2018)
This research aimed to study the influence of phosphate fertilizer and plant growth regulator applications on the growth and yield of ratoon rice grown on swampland. The research was conducted in September 2016 to January 2017 at the greenhouse of Department of Soil Science, Faculty of Agriculture, Sriwijaya University. Soil characteristics were analyzed in the Laboratory of Chemistry, Biology and Soil Fertility, Department of Soil Science, Faculty of Agriculture, Sriwijaya University. The experiment was arranged in a factorial Completely Randomized Design.Â The first factor was the phospate fertilizer dosages, i.e. 150 kg ha-1 (P1), 200 kg ha-1 (P2), 250 kg ha-1 (P3). The second factor was the plant growth regulator treatments, consisting of control (Z0), Cytokinin 20 ppm (Z1), Gibberellin 60 ppm (Z3). The results showed that the application of P fertilizer did not affect the yield and growth of ratoon rice. However, the application of Plant Growth Regulators resulted in a significant effect on the growth and yield of ratoon rice. The application of Plant Growth Regulator of Gibberellin with the dosage of 60 ppm was able to increase the percentage of filled grains (84.93%), decrease the percentage of empty grains (15.07%), increase the weight of 100 grains (3.63 g) and increase the dry weight ofÂ milled grains (7.80 Mg ha-1). It is suggested that the treatment resulted in better plant growth and yield obtained in the current study might be recommended for ratoon cultivation in swampland.